Hydrogen isotope fractionation of leaf wax n-alkanes in southern African soils. (July 2017) - Herrmann, Nicole; Boom, Arnoud; Carr, Andrew S.; Chase, Brian M.; West, Adam G.; Zabel, Matthias; Schefuß, Enno
Highlights: δDwax in southern African soils reflects δD of precipitation in summer rainfall zone. Apparent hydrogen isotope fractionation in this area is affected by evapotranspiration. Relation of δDwax with δD of precipitation in winter rainfall zone remains unclear. High micro-climatic variability in winter rainfall zone compromises a clear distinction of environmental influences. Abstract: The hydrogen isotope composition of plant leaf wax (δDwax ) has been found to record the isotope composition of precipitation (δDp ). Hence, δDwax is increasingly used for palaeohydrological reconstruction. It is, however, also affected by secondary factors, such as vegetation type, evapotranspiration and environmental conditions, complicating its direct application as a quantitative palaeohydrological proxy. Here, we present δDwax data from soils along vegetation gradients and climatic transects in southern Africa to investigate the impact of different environmental factors on δDwax . We found that δDwax correlated significantly with annual δDp (obtained from the interpolated Online Isotopes in Precipitation Calculator data set) throughout eastern and central South Africa, where the majority of the mean annual precipitation falls during the summer. We found evidence for the effect of evapotranspiration on δDwax, while vegetation change was of minor importance. In contrast, we found that δDwax did not correlate with annual δDp in western and southwestern South Africa, where most of the annual precipitation falls during winter. Wide microclimatic variability in this topographically variable region, including distinct vegetation communities and high vegetation diversity between biomes as well as a potential influence of summer rain in some locals, likely compromised identification of a clear relationship between δDwax and δDp in this region. Our findings have implications for palaeoenvironmental investigations using δDwax in southern Africa. In the summer rain dominated eastern and central region, δDwax should serve well as a qualitative palaeohydrological recorder. In contrast, the processes influencing δDwax in the winter rain- dominated western and southwestern South Africa remain unclear and, pending further analyses, potentially constrain its use as palaeohydrological proxy in this region.